Inovação tecnológica nas empresas no setor de biotecnologia no Brasil - Chu, Daniel Martinelli (2009)
The goal of this study is to contribute to the understanding of the technological innovation process in Brazilian biotechnology firms. To achieve that, the study sought to: identify the most critical factors to the innovation process of the firms in this sector; analyze the sector’s dynamics and the contribution of universities and incubators to the innovation process and; evaluate how these elements affect the management process on technological innovation inside and outside the boundaries of the organization. This exploratory study with qualitative approach was based on multiple case study methodology and the results were interpreted using content analysis technique, as well as the analysis of secondary data. The study indicated that among the many obstacles to innovation, access to financial assets is the most critical. Partnerships, pointed as an alternative to this and other problems by reducing investments and risks and by providing access to qualified workforce, equipments and sophisticated laboratories, have been hindered by a series of institutional and regulatory factors – starting by the lack of clear laws and rules regarding intellectual property. On top of this there is still an incipient collaborative culture among firms. The results of the study show that Brazilian biotechnology firms try to compensate theses obstacles by providing agility to its internal processes, creating flexible organizational structures and an organizational environment favorable to innovation, which is internalized as practice in a tacit way. The management of innovation happens in an informal and little systematic way. Finally, the results show that the process of innovation in Brazilian biotechnology firms takes advantage of a pro-active attitude of managing and learning with the adversities adopted by these firms.